2020
DOI: 10.1093/scipol/scaa066
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the relevance of science for practice and practice for science: Quantitative empirical insights

Abstract: We present results of a survey conducted with researchers and practitioners involved in a Swiss National Research Programme on steering energy consumption. We analyse what motivates practitioners and researchers to engage in a collaborative research project, their perception of the collaboration intensity in different project phases, and the extent to which the research project provided useful results for practitioners. Our analyses demonstrate that the intensity of collaboration is a key driver of successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Actually, the limited participation from outside academia at IPW9—as mentioned above—illustrated this deficiency directly. This is unfortunate since Binder et al (Binder et al 2020 ) found that the benefit of scientific results was perceived to be higher the more interactions took place between practice and science. Higher interaction lead to higher trust and the feeling that one can support the results and that their applicability is higher (Binder et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Actually, the limited participation from outside academia at IPW9—as mentioned above—illustrated this deficiency directly. This is unfortunate since Binder et al (Binder et al 2020 ) found that the benefit of scientific results was perceived to be higher the more interactions took place between practice and science. Higher interaction lead to higher trust and the feeling that one can support the results and that their applicability is higher (Binder et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is unfortunate since Binder et al (Binder et al 2020 ) found that the benefit of scientific results was perceived to be higher the more interactions took place between practice and science. Higher interaction lead to higher trust and the feeling that one can support the results and that their applicability is higher (Binder et al 2020 ). Therefore, we summarize a number of recommendations brought forward during the workshop to improve on the science—practice/policy interactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations